Feature-Based Probabilistic Data Association for Video-Based Multi-Object Tracking - Grinberg, Michael (KIT Scientific Publishing, 2018)
This work proposes a feature-based probabilistic data association and tracking approach (FBPDATA) for multi-object tracking. FBPDATA is based on re-identification and tracking of individual video image points (feature points) and aims at solving the problems of partial, split (fragmented), bloated or missed detections, which are due to sensory or algorithmic restrictions, limited field of view of the sensors, as well as occlusion situations.
English
Keywords: gestörte Detektionenfeature-based; probabilistic; merkmalsbasiert; probabilistisch; Datenassoziation; object tracking; corrupted detections; data association; Objektverfolgung